Decreasing Coalbed Methane Formation Damage Using Microfoamed Drilling Fluid Stabilized by Silica Nanoparticles. (18th January 2016) - Cai, Jihua; Gu, Sui; Wang, Fawen; Yang, Xianyu; Yue, Ye; Wu, Xiaoming; Chixotkin, V. F.
Abstract : Coalbed methane (CBM) reservoirs in China are featured in remarkable nanosized pores below 200 nm, acknowledged natural cleats, and tectonic fractures. This paper discussed the possibility that a clay free microfoamed drilling fluid could be stabilized by silica nanoparticles (CFMDF-NP) so as to avoid formation damage of CBM drilling. In accordance with the experimental results of foaming capacity and foam stability test, basic drilling fluid performance appraisal, micromorphology observation, swelling test, and gas permeability test, the mechanism of the CFMDF-NP was discussed in this paper. The results indicated that, with 10–20 nm nano-SiO2, the foaming volume of traditional foamed drilling fluid could be improved by up to 50% and an increased half-life period by up to 200%. Chemically treated nano-SiO2 dispersions functioned as a foam stabilizer and a foaming agent as well. The CFMDF-NP had controllable density (0.7 1 g/cm 3 ) and excellent rheological and sealing properties, which could satisfy the drilling requirements of the low pressure coal seams. With 5–8 mm slicing on the contaminated side of coal cores, the contaminated zone could be removed and the recovery rate of gas permeability could reach up to 70%. The CFMDF-NP laid good technical foundation to decrease formation damage of CBM reservoir.